The Character Education Value Within The Everest Film - Wiwik, Wiwik; Ro'is, Syamsuddin; Harida, Ratri (Jurnal Bahasa dan Sastra, 2025)
Character education is the method to create the student’s personalities becoming a good human. This study aims to describe of the character education in The Everest film and to explain the impact this study with the education in general. The researcher chooses a descriptive method to analyze the data. The researcher use qualitative approach, which the data from of written or oral words that is descriptively analyzed. Technique of collecting data in this research is qualitative descriptive analysis technique. In The Everest film, the researcher finds out eleven character education values, comprised of religious, honest, social care, discipline, love, hard work, respect to the achievement, communicative, responsible, autonomous and tolerance. Based on the analysis, there were two of religious values, four of honest values, three tolerance values, ten of social cares values, three of discipline values, two of respect to the achievement values, friendly value, two of love value, and two of responsible values. The impacts of the movie in education are; it gives an inspiration on how to be passionate on one’s ambition, it teaches the students to care for other students, teacher, and the society, it teaches us to study hard and work seriously.